Ductile Copolyesters Prepared Using Succinic Acid, 1,4-Butanediol, and Bis(2-hydroxyethyl) Terephthalate with Minimizing Generation of Tetrahydrofuran - Park, Sang Uk; Seo, Hyeon Jeong; Seo, Yeong Hyun; Park, Ju Yong; Kim, Hyunjin; Cho, Woo Yeon; Lee, Pyung Cheon; Lee, Bun Yeoul (Polymers, 2024)
Poly(1,4-butylene succinate) (PBS) is a promising sustainable and biodegradable synthetic polyester. In this study, we synthesized PBS-based copolyesters by incorporating 5–20 mol% of –O2CC6H4CO2– and –OCH2CH2O– units through the polycondensation of succinic acid (SA) with 1,4-butanediol (BD) and bis(2-hydroxyethyl) terephthalate (BHET). Two different catalysts, H3PO4 and the conventional catalyst (nBuO)4Ti, were used comparatively in the synthesis process. The copolyesters produced using the former were treated with M(2-ethylhexanoate)2 (M = Mg, Zn, Mn) to connect the chains through ionic interactions between M2+ ions and either –CH2OP(O)(OH)O− or (–CH2O)2P(O)O− groups. By incorporating BHET units (i.e., –O2CC6H4CO2– and –OCH2CH2O–), the resulting copolyesters exhibited improved ductile properties with enhanced elongation at break, albeit with reduced tensile strength. The copolyesters prepared with H3PO4/M(2-ethylhexanoate)2 displayed a less random distribution of –O2CC6H4CO2– and –OCH2CH2O– units, leading to a faster crystallization rate, higher Tm value, and higher yield strength compared to those prepared with (nBuO)4Ti using the same amount of BHET. Furthermore, they displayed substantial shear-thinning behavior in their rheological properties due to the presence of long-chain branches of (–CH2O)3P=O units. Unfortunately, the copolyesters prepared with H3PO4/M(2-ethylhexanoate)2, and hence containing M2+, –CH2OP(O)(OH)O−, (–CH2O)2P(O)O− groups, did not exhibit enhanced biodegradability under ambient soil conditions.
Keywords: Biodegradable; Bis(2-hydroxyethyl)terephthalate; Butanediol; Copolyesters; PBS; Poly(1,4-butylene succinate); Polycondensations; Succinic acids; Tetra-hydrofuran; Tetrahydrofurans; biodegradable; bis(2-hydroxyethyl) terephthalate; copolyester; PBS; poly(1,4-butylene succinate); polycondensation